RETRACTED: Analyzing Intention to Purchase Brand Extension via Brand Attribute Associations: The Mediating and Moderating Role of Emotional Consumer-Brand Relationship and Brand Commitment - Bian, Weijun; Yan, Gong (Frontiers in Psychology, 2022)
The aim of this study is to investigate the drivers of brand extension attributes and its impact on intention to purchase brand extensions mediated by emotional consumer-brand relationship (ECBR). Data was collected from Chinese university students with the help of questionnaire. Structure equation modelling was applied with the help of AMOS to analyze collected data. Results depict that brand attribute association has significant impact on intention to purchase luxury brands extension. Results further explain that emotional consumer-brand relationship mediates the relationship between brand attribute associations and purchase intention of brand extensions. Furthermore, results indicate that brand commitment moderates the relationship between brand attribute associations, emotional consumer-brand relationship and intention to purchase brand extensions. This study provides an intensive knowledge of the association that exists between the intent to buy luxury brands’ extension and ECBR. This study focuses on the heart versus mind distinction, which is integral to the research on the relationship between consumers and brands. This study provides useful insights to brand managers to use strategies that enhance the bond between emotional and cognitive factors customers associate with a particular brand. Luxury brand managers ought to balance emotionality and rationality to create and capitalize on unique associations with customers.